2015
DOI: 10.1088/0951-7715/28/5/1307
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar solutions of the one-dimensional Landau–Lifshitz–Gilbert equation

Abstract: The main purpose of this paper is the analytical study of self-shrinker solutions of the one-dimensional Landau-Lifshitz-Gilbert equation (LLG), a model describing the dynamics for the spin in ferromagnetic materials. We show that there is a unique smooth family of backward self-similar solutions to the LLG equation, up to symmetries, and we establish their asymptotics. Moreover, we obtain that in the presence of damping, the trajectories of the self-similar profiles converge to great circles on the sphere S 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 56 publications
(120 reference statements)
0
30
0
Order By: Relevance
“…In the one-dimensional case N = 1, we established in [17] the existence and asymptotics of the family {m c,α } c>0 of self-similar solutions of (LLG α ) for any fixed α ∈ [0, 1], extending the results in Gutiérrez, Rivas and Vega [18] in the setting of the Schrödinger map equation and related binormal flow equation. The motivation for the results presented in this paper first originated from the desire to study further properties of the self-similar solutions found in [17], and in particular their stability. In the case α = 0, the stability of the self-similar solutions of the Schrödinger map has been considered in the series of papers by Banica and Vega [5,6,7], but no stability result is known for these solutions in the presence of damping, i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…In the one-dimensional case N = 1, we established in [17] the existence and asymptotics of the family {m c,α } c>0 of self-similar solutions of (LLG α ) for any fixed α ∈ [0, 1], extending the results in Gutiérrez, Rivas and Vega [18] in the setting of the Schrödinger map equation and related binormal flow equation. The motivation for the results presented in this paper first originated from the desire to study further properties of the self-similar solutions found in [17], and in particular their stability. In the case α = 0, the stability of the self-similar solutions of the Schrödinger map has been considered in the series of papers by Banica and Vega [5,6,7], but no stability result is known for these solutions in the presence of damping, i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 71%
“…there exists a unique solution m ∈ X(R N × R + ; S 2 ) of (LLG α ) with initial condition m 0 such that 3 We refer the reader to Theorem A.5 in the Appendix and to [17] for precise statements of these results. 4 See footnote in Section 3.3 for the definition of the Morrey space M 2,2 (R N ).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations